Prediction of Mold Spoilage for Soy/Polyethylene Composite Fibers - Chinmay Naphade; Inyee Han; Sam Lukubira; Amod Ogale; James Rieck; Paul Dawson (International Journal of Polymer Science)
Mold spoilage was determined over 109 days on soy/PE fibers held under controlled temperatures (T) ranging from 10°C to 40°C and water activities (aw) from 0.11 to 0.98. Water activities were created in sealed containers using saturated salt solutions and placed in temperature-controlled incubators. Soy/PE fibers that were held at 0.823 aw or higher exhibited mold growth at all temperatures. As postulated, increased water activity (greater than 0.89) and temperature (higher than 25°C) accelerated mold growth on soy/PE fibers. A slower mold growth was observed on soy/PE fibers that were held at 0.87 aw and 10°C. A Weibull model was employed to fit the observed logarithmic values of T, aw, and an interaction term log⁡T×log⁡aw and was chosen as the final model as it gave the best fit to the raw mold growth data. These growth models predict the expected mold-free storage period of soy/PE fibers when exposed to various environmental temperatures and humidities.